Efektivitas Layanan Konseling Kelompok dengan Teknik Expressive Writing dalam Mengelola Repressed Anger pada Remaja di MTs Swasta Al-Ulum Medan - Suci Permata Hati; Alfin Siregar (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2025)
Adolescence is characterized by high emotional intensity with immature regulatory abilities, making it vulnerable to repressed anger, which can lead to neurotic symptoms, psychosomatic disorders, and maladaptive behavior. This study aims to test the effectiveness of group counseling with expressive writing* techniques in managing repressed anger in Indonesian adolescents. This quasi-experimental study with a nonequivalent control group pretest-posttest design involved 20 seventh-grade students of MTs Swasta Al-Ulum Medan, divided through matching-randomization into experimental and control groups. The instrument used was a 48-item repressed anger scale of 0.961. The results showed that the experimental group experienced a very significant decrease from M 174.40 to M 147.00 t9 14.707, p 0.001, while the control group showed no significant change. The intergroup test confirmed a significant difference t18 12.822, p 0.001. These findings confirm that the integration of expressive writing in group counseling is effective and relevant to be implemented in Guidance and Counseling services in schools.